Clinical outcomes after percutaneous coronary intervention in patients with coronary artery disease: six months results from a single centre study - Reddy, L. Kiran Kumar; Satheesh, Santhosh (International Journal of Research in Medical Sciences, 2019)
Background: The study aimed to evaluate clinical outcomes in patients with coronary artery diseases (CAD) who underwent percutaneous coronary intervention (PCI), to identify the factors associated with clinical outcomes and survival among such patients, to explore the procedure related complications, and to assess restenosis and stent thrombosis rates following PCI. Methods: This retrospective, single-center, observational study was conducted at a tertiary-care center in India, which included patients with CAD undergoing PCI from January 2016 to December 2016. Angiographic and clinical success and complications related to both procedural and vascular access were noted. Patient were followed-up for clinical outcomes up to 6-months. Primary outcome of the study was all-cause mortality. Secondary outcome measures were cardiovascular mortality, and event free survival, angina, cardiovascular events and restenosis and stent thrombosis. Results: A total of 831 patients were included of which majority were males (83.5%). Smoking was found in 33.7%, diabetes in 35.6%, and hypertension in 37.7%. At 6-months, follow-up was obtained for 711 patients. The clinical composite endpoint seen in 9.8% of patients. Angina (13.2%), acute coronary syndrome (3.1%), stent thrombosis (1.0%), in-stent restenosis (3.9%), cardiovascular and all-cause mortality (2.7%), heart failure (7.3%) and stroke (1.7%) were reported at 6-months follow-up. Conclusions: The PCI in a tertiary-care centre leads to low rates of periprocedural events and low rates of clinical outcomes at 6-months follow-up. Moreover, left ventricular ejection fraction was shown to be major predictor for cardiovascular mortality in post-PCI patients. Hypertension was significantly associated with stroke post-PCI.